Identifying the Immediate and Remote Causes of Pipeline Disasters in Nigeria (Global Journal of Science Frontier Research, 2020)
Several occurrences of the transport system of the natural gold vandalisms in Nigeria, especially in the Niger Delta part of Nigeria is so upfront and seem neverending. However, this seemed also to be a result of many factors ranging from the unemployment of youths and the inadequate management and necessary government policies to be put in place to ensure guaranteed security. Past researchers have observed and given the fact that the major causes of this disaster are attached to a technical fault and some failures in aging, corrosion, and mechanical challenges like those welding effects. This research work examined immediate and remote causes of pipeline disasters considering the dimension of factors, the level of preparedness of people for the pipeline disasters, and the risk perception of people, the socioeconomic characteristics and the destruction of the pipelines.
Keywords: oil spill; oil theft; pipeline attacks vandalism interdiction; GIS; environmental impact mitigation; data; nigeria